2004
DOI: 10.4049/jimmunol.173.5.3215
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of −571 IL-10 Promoter Polymorphism Reveals a Repressor Element Controlled by Sp1

Abstract: Transcriptional dysregulation of the IL-10 gene may contribute to the development and severity of autoimmune, infectious, neoplastic, and allergic diseases. A C to A base substitution has been identified at −571 bp in the IL-10 promoter and has been linked to immune diseases. The role of this polymorphism in IL-10 promoter function was assessed using luciferase reporter constructs. The presence of an A at −571 (A allele) increases promoter activity compared with that of a promoter with a C at this position (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 63 publications
2
38
1
Order By: Relevance
“…The -571 base exchange occurs between what we confirmed as being an Sp family member binding site and a sequence with similarity to that recognized by members of the ets family (AGGAA) [19]. The transcription factor(s) that specifically binds to this region of the IL-10 promoter has not yet been identified, however, the binding affinity of this factor was influenced by the C-to-A base exchange (unpublished data).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The -571 base exchange occurs between what we confirmed as being an Sp family member binding site and a sequence with similarity to that recognized by members of the ets family (AGGAA) [19]. The transcription factor(s) that specifically binds to this region of the IL-10 promoter has not yet been identified, however, the binding affinity of this factor was influenced by the C-to-A base exchange (unpublished data).…”
Section: Discussionsupporting
confidence: 61%
“…Specifically, it has been demonstrated that the C-to-A nucleotide exchange at position -571 results in increased promoter activity in B cells and that the transcription factors Sp1 and Sp3 can bind to a region immediately upstream of the polymorphism. The region including the Sp1/Sp3 site and adjoining polymorphism functions as a transcriptional repressor, and the Cto-A base exchange relieves the repression mediated by Sp1 [19]. We demonstrated that the A allele was associated with elevated total serum IgE in subjects heterozygotic or homozygotic for this base exchange [20].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…38 LPS activates the three mitogen-activated protein kinase (MAPK9) pathways ERK, JNK and p38 and, thereby, transcription factors that are involved in gene regulation. 35 Chanteux et al 35 showed that ERK, p38, JNK as well as Sp1 are essential in LPS-induced IL-10 expression in human alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…33 This binding site is present in both reporter plasmids, GCC and ACC. DG75 B cells were transfected with the GCC and ACC reporter plasmids and subsequently incubated with or without LPS.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 98%